Chapter 13 Ethical Hotspots in Infectious Disease Surveillance for Global Health Security Social justice and Pandemic Preparedness - Parker, Michael (Oxford University Press, 2023)
At the time of writing, the world remains in the grip of the COVID-19 pandemic. Approximately 14.9 million people have died and every country in the world has been affected affectedaffectedaffectedaffected directly or indirectly (WHO 2022a). This, This,together with recent experiences of Ebola and Zika, has led to calls for the development and implementation of international strategies for pandemic preparedness, response, and prevention.